2013
DOI: 10.1021/nl4010817
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Spinning of Gold Nanoparticles in Water Using Circularly Polarized Light

Abstract: Controlling the position and movement of small objects with light is an appealing way to manipulate delicate samples, such as living cells or nanoparticles. It is well-known that optical gradient and radiation pressure forces caused by a focused laser beam enables trapping and manipulation of objects with strength that is dependent on the particle's optical properties. Furthermore, by utilizing transfer of photon spin angular momentum, it is also possible to set objects into rotational motion simply by targeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
165
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(170 citation statements)
references
References 39 publications
5
165
0
Order By: Relevance
“…25,45,[76][77] Figure 7a illustrates that this method can be used to spin large gold colloids (average radius ~200 nm) about their own axes with frequencies of the order of 3 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 27 kHz or more, the highest reported to date for particles in water. 45 The particles were trapped in 2D, using a λ = 830 nm laser beam with a power of ~10-50 mW at the sample, and the spinning was revealed by measuring the intensity autocorrelation of light scattered from the trapped particle: the correlation function exhibits a periodic oscillation when the particle spins due to SAM transfer from circularly polarized light, whereas it decays monotonously for linearly polarized light. Comparisons with theory indicated that the high spinning frequencies observed experimentally were partly due to particle heating and a corresponding decrease of the viscous torque by the water surrounding the particles.…”
Section: Alignement and Rotation Of Plasmonic Nanostructuresmentioning
confidence: 99%
“…25,45,[76][77] Figure 7a illustrates that this method can be used to spin large gold colloids (average radius ~200 nm) about their own axes with frequencies of the order of 3 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 27 kHz or more, the highest reported to date for particles in water. 45 The particles were trapped in 2D, using a λ = 830 nm laser beam with a power of ~10-50 mW at the sample, and the spinning was revealed by measuring the intensity autocorrelation of light scattered from the trapped particle: the correlation function exhibits a periodic oscillation when the particle spins due to SAM transfer from circularly polarized light, whereas it decays monotonously for linearly polarized light. Comparisons with theory indicated that the high spinning frequencies observed experimentally were partly due to particle heating and a corresponding decrease of the viscous torque by the water surrounding the particles.…”
Section: Alignement and Rotation Of Plasmonic Nanostructuresmentioning
confidence: 99%
“…Despite such restraints, researchers have developed various ways to produce optical torque on the nanoscale: the principles in creating structurally asymmetric metallic rotors [29,30] have been scaled down to the nanoscale by enhancing the optical response of subwavelength particles through the excitation of surface plasmon (SP) resonance [31,32]. Researchers have also demonstrated kHz-rate spinning of gold nanospheres in water by the absorptive transfer of SAM from circularly polarized light [33]. SP resonance has also been widely used in designing nanoscale optical elements, inside systems for the spatial modulation of light such as optical nanotweezers [34][35][36][37][38], optical antennas [39,40], and OAM-mediating metasurfaces [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…We have further demonstrated a more detailed understanding of thermal effects in the dynamics of optically trapped airborne gold NPs. US gold particles can pave the way for more controlled studies of SERS, plasmon mediated optical binding, spin angular momentum transfer 16,30 and may even perform as efficient handles for manipulation. 13 Furthermore, trapping of such US particles in air or a vacuum may open up new opportunities in levitated optomechanics.…”
Section: Discussionmentioning
confidence: 99%
“…11 Importantly US NPs exhibit about a two-fold reduction in the measurement error (σ rms ) for stiffness (see Table II) compared to NS counterparts due to the improved circularity of US gold NPs (see Table I). We note that when trapped with a circularly polarized beam, one can expect laserinduced rotation of gold NPs, 16 in which case the stiffness is averaged over azimuth angles. Thus linearly polarized beam traps may result in more a pronounced difference in stiffness between US and NS gold NPs.…”
Section: B Trapping In Liquidmentioning
confidence: 94%